(untitled) (Global Journal of Human-Social Science, 2020)
The Anals who reside mostly in the south-eastern parts of Manipur are one of the oldest tribes of Manipur. They have been recognized as the tribe of India since 1951. In this paper the author presents a comprehensive study of the customary laws that the Anals practice in the past and at present. The study focuses on the various aspects of the Anal customary laws and its relevance. The paper presents an overview of the various customary laws that the Anals follow and provides us with a clearer understanding of the Anal tribe.